O setor de gás natural no Brasil: Uma comparaç\~ao com os países da OCDE - Maria Bernadete Gomes Pereira Sarmiento Gutierrez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Organisation for Economic Co-operation and Development (OECD) countries have promoted important reforms in the natural gas sector, in a similar way as in their electricity sectors, breaking the prevailing vertical integration model, characterised by territorial monopolies. The 2021 New Gas Law is the result of earlier attempts to liberalise the natural gas sector in Brazil, allowing its expansion with the expected result of increasing its participation in the Brazilian energy matrix, following a reduction in prices. In this context, a comparative analysis of OECD PMR indicators for the natural gas sector is undertaken, in order to compare the differences between Brazil and OECD countries in order to provide subsidies for further reforms.
Keywords: L51; L95; 330; natural gas sector; liberalisation; New Gas Law